Induced sputum in the diagnosis of childhood community-acquired pneumonia. Issue 3 (3rd December 2008) - Lahti, E; Peltola, V; Waris, M; Virkki, R; Rantakokko-Jalava, K; Jalava, J; Eerola, E; Ruuskanen, O
Abstract : Background: The usefulness of induced sputum in searching for causative agents of pneumonia in children has not been studied. Methods: The study involved 101 children, aged 6 months to 15 years, treated for community-acquired pneumonia at Turku University Hospital (Turku, Finland) from January 2006 to April 2007. Nasopharyngeal aspirate samples were first collected through both nostrils. Sputum production was then induced by inhalation of 5.0% hypertonic saline for 5–10 min and a sputum sample was either aspirated or expectorated. The presence and amount of bacteria and viruses in paired nasopharyngeal aspirate and sputum specimens was analysed and compared using semiquantitative bacterial culture and quantitative PCR techniques. Results: A good quality sputum specimen was obtained from 76 children. The possible causative agent was found in 90% of cases. Streptococcus pneumoniae (46%) and rhinovirus (29%) were the most common microbes detected. Newly discovered viruses human bocavirus and human metapneumovirus were detected in 18% and 13% of the children, respectively. One-quarter of all bacterial findings were only detected in sputum, and the amount of bacteria in the remainder of the sputum specimens compared with nasopharyngeal aspirate was higher in 14% and equal in 70%. The amount of rhinovirus in sputum was higher than in nasopharyngeal aspirate in 82%. Conclusions: Sputum induction provides good quality sputum specimens with high microbiological yield in children with community-acquired pneumonia. Induced sputum analysis can be useful in the microbiological diagnosis of childhood community-acquired pneumonia.